(untitled) (KYAMC Journal, 2017)
This study was carried out on the new patient’s who attended the out patients department (OPD) of Pabna Mental Hospital during the calendar year 2008. Data was collected from 211(two hundred and eleven) patients among the new patient’s attended during the study period. Male patients were 49.76% and the Females were 50.24%. The age of the patients ranges from one year and six months to hundred and twenty (120) years. The mean age was 32.33 for the total and 34.88 for the males and 29.82 for the females. Among the respondents, 11 to 40 years age group suffers more and 97.63% cases were Muslims and the rest were Hindus. Illiterate were more (38.39%) than other individual educational groups. Number of nuclear family was 58.77%. Majority of the patients (43.11%) have living house and land to cultivate. More than half (60.66%) have family income below Tk. 5000/- per month. Almost all (90.99%) were from rural background. Schizophrenia (28.92%) and Anxiety Disorder (23.70%) occupies more than half (52.61%) of the respondents. Majority (86.73%) do not have any family history of mental illness. Most of the respondents (36.49%) have given the history of taking mixed type of treatment (Folk, Homoeo, Rural medical practitioner, Doctor, Specialist) before attending the Mental Hospital. KYAMC Journal Vol. 5, No.-2, Jan 2015, Page 509-513